2021
DOI: 10.1371/journal.pone.0259893
|View full text |Cite
|
Sign up to set email alerts
|

The burden of SARS-CoV-2 among healthcare workers across 16 hospitals of Kashmir, India—A seroepidemiological study

Abstract: SARS-CoV-2 pandemic has greatly affected healthcare workers because of the high risk of getting infected. The present cross-sectional study measured SARS-CoV-2 antibody in healthcare workers of Kashmir, India. Methods: Serological testing to detect antibodies against nucleocapsid protein of SARS-CoV-2 was performed in 2003 healthcare workers who voluntarily participated in the study. Results: We report relatively high seropositivity of 26.8% (95% CI 24.8–28.8) for SARS-CoV-2in healthcare workers, nine months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, the seropositivity to SARS-CoV-2 may noticeably fluctuate depending on different parameters such as geographical location and the time when the research was conducted (stage of the pandemic), timeliness and the enforcement of infection control measures, the sampling strategies and type of serological test used, and may progressively increase over time. Therefore, it is not surprising that in our study, which was conducted later during the pandemic, after the sixth epidemic wave of COVID-19 and more than one year since the beginning of the vaccination campaigns in Serbia and elsewhere, the observed prevalence was much higher compared to the prevalence rates obtained in various populations of HCWs in several other SARS-CoV-2 seroprevalence studies that were performed before the period of our research [2,[16][17][18][19][20][21][22][23][24][25]. In addition, numerous previous studies reported that the seroprevalence to SARS-CoV-2 among HCWs was higher in comparison with the general population [4,17,26,27].…”
Section: Discussionmentioning
confidence: 51%
“…Thus, the seropositivity to SARS-CoV-2 may noticeably fluctuate depending on different parameters such as geographical location and the time when the research was conducted (stage of the pandemic), timeliness and the enforcement of infection control measures, the sampling strategies and type of serological test used, and may progressively increase over time. Therefore, it is not surprising that in our study, which was conducted later during the pandemic, after the sixth epidemic wave of COVID-19 and more than one year since the beginning of the vaccination campaigns in Serbia and elsewhere, the observed prevalence was much higher compared to the prevalence rates obtained in various populations of HCWs in several other SARS-CoV-2 seroprevalence studies that were performed before the period of our research [2,[16][17][18][19][20][21][22][23][24][25]. In addition, numerous previous studies reported that the seroprevalence to SARS-CoV-2 among HCWs was higher in comparison with the general population [4,17,26,27].…”
Section: Discussionmentioning
confidence: 51%
“…All vaccines follow the same basic principle, pre-exposing the immune system of a person to either killed or weakened pathogens, or some of the pathogen's structural parts, which leads the body to elicit an immune response (9). Similar to infection, vaccines result in early production of serum immunoglobulin (Ig)A, IgM and IgG antibodies, and also induce long-lasting memory B-and T-cell responses (10)(11)(12). Adenoviral vaccines are those in which viral gene delivery systems rely on a host viral genome (e.g., adenovirus) that typically lacks the genetic components necessary to produce new virions and that encodes antigenic components of the virus of interest to elicit a protective immune response, primarily through virus-neutralizing antibodies specific for spike protein of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%